Design of a Novel Ring Current Controlled Oscillator with low Phase Noise and High frequency range Using Nanowire Transistor - Khalaj, M (International Journal of Computer Sciences and Engineering, 2025)
In this paper a ring CURRENT CONTROLLED OSCILLATOR with high frequency range and low phase noise in Nanowire transistor technology is presented. In the proposed CURRENT CONTROLLED OSCILLATOR, two techniques including control of current and body bias technique is implemented to increase the range of frequency. It is proved that body bias of control transistor cause to increase the frequency range noticeably. Moreover, by adding an inductor in the body of control transistor, the phase noise is decreased as well. The phase noise in 1 MHz offset frequency is -90 dBc/Hz and the frequency range is 2-14 GHz.